2006
DOI: 10.1111/j.1742-4658.2006.05256.x
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular localization of vaccinia‐related kinase‐2 (VRK2) isoforms determines their different effect on p53 stability in tumour cell lines

Abstract: VRK is a new kinase family of unknown function. Endogenous human vacinia‐related kinase 2 (VRK2) protein is present in both the nucleus and the cytosol, which is a consequence of alternative splicing of two VRK2 messages coding for proteins of 508 and 397 amino acids, respectively. VRK2A has a C‐terminal hydrophobic region that anchors the protein to membranes in the endoplasmic reticulum (ER) and mitochondria, and it colocalizes with calreticulin, calnexin and mitotracker; whereas VRK2B is detected in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
1
32

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(183 citation statements)
references
References 69 publications
(123 reference statements)
6
144
1
32
Order By: Relevance
“…2D), although their appearance was slightly different from that in HEK293T cells. Endogenous VRK1 is mostly located within the nucleus (24,40), but in some cell types a subpopulation is also detected in the cytosol (7,37) or in cytosolic vesicles and the Golgi apparatus (38). These data suggested that at least a subpopulation of endogenous VRK1 and Plk3 proteins might form an intracellular particulate complex.…”
Section: Resultsmentioning
confidence: 78%
“…2D), although their appearance was slightly different from that in HEK293T cells. Endogenous VRK1 is mostly located within the nucleus (24,40), but in some cell types a subpopulation is also detected in the cytosol (7,37) or in cytosolic vesicles and the Golgi apparatus (38). These data suggested that at least a subpopulation of endogenous VRK1 and Plk3 proteins might form an intracellular particulate complex.…”
Section: Resultsmentioning
confidence: 78%
“…The subcellular localization of protein codified from this gene is dependent on two alternatively spliced variants (Blanco et al, 2006). Other alternative splicing messages have been detected but no proteins have been identified expressed from these alternative messages in humans.…”
Section: Dna/rnamentioning
confidence: 99%
“…VRK2 protein has two isoforms: VRK2A isoform is a 508 amino acid 58.141 KDa protein and VRK2B isoform, a 397 amino acid 45.030 KDa protein (Blanco et al, 2006). Both isoforms present a serine-threonine kinase domain (residues 29-266) with an ATP-binding site (residues 36-61) and three active kinase motifs (residues 164-168, 184-188 and 218-220).…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations